Acetylcholinesterases - the structural similarities and differences - Wiesner, Jiří; Kříž, Zdeněk; Kuča, Kamil; Jun, Daniel; Koča, Jaroslav (Journal of enzyme inhibition and medicinal chemistry, 2007)
Acetylcholinesterase (AChE) is a widely spread enzyme playing a very important role in nerve signal transmission. As AChE controls key processes, its inhibition leads to the very fast death of an organism, including humans. However, when this feature is to be used for killing of unwanted organisms (i.e. mosquitoes), one is faced with the question - how much do AChEs differ between species and what are the differences? Here, a theoretical point of view was utilized to identify the structural basis for such differences. The various primary and tertiary alignments show that AChEs are very evolutionary conserved enzymes and this fact could lead to difficulties, for example, in the search for inhibitors specific for a particular species.
Keywords: molekulární konformace; molekulární evoluce; signální transdukce; Molecular Conformation; Signal Transduction; Drosophila melanogaster; Humans; sekvenční homologie aminokyselin; Sequence Homology, Amino Acid; Molecular Sequence Data; Evolution, Molecular; molekulární sekvence - údaje; sekvence aminokyselin; Protein Conformation; financování organizované; konzervovaná sekvence; Financing, Organized; vazebná místa; lidé; zvířata; myši; Binding Sites; Mice; Protein Folding; Amino Acid Sequence; Conserved Sequence; sbalování proteinů; Acetylcholinesterase; Animals; acetylcholinesterasa; konformace proteinů